The interleukin-1 cytokine family members: Role in cancer pathogenesis and potential therapeutic applications in cancer immunotherapy. (December 2021) - Boersma, Bart; Jiskoot, Wim; Lowe, Peter; Bourquin, Carole
Abstract: The interleukin-1 (IL-1) family is one of the first described cytokine families and consists of eight cytokines (IL-1β, IL-1α, IL-18, IL-33, IL-36α, IL-36β, IL-36γ and IL-37) and three receptor antagonists (IL-1Ra, IL-36Ra and IL-38). The family members are known to play an essential role in inflammation. The importance of inflammation in cancer has been well established in the past decades. This review sets out to give an overview of the role of each IL-1 family member in cancer pathogenesis and show their potential as potential anticancer drug candidates. First, the molecular structure is described. Next, both the pro- and anti-tumoral properties are highlighted. Additionally, a critical interpretation of current literature is given. To conclude, the IL-1 family is a toolbox with a collection of powerful tools that can be considered as potential drugs or drug targets.